EFFECT OF MIKANIA CORDATA ON NON-SPECIFIC IMMUNE RESPONSE AND SURVIVAL OF LABEO ROHITA AGAINST APHANOMYCES INVADANS - V. Kumar; S. Roy; D. Barman (Journal of Animal and Plant Sciences, 2016)
The study was conducted to evaluate the efficacy of Mikania cordata leaf powder on non-specific immune response and disease resistance of Labeo rohita fingerlings against the Aphanomyces invadans infection. M. cordata extract was incorporated in the diets (at 0.0%, 1%, 2% and 3%) of L. rohita fingerlings (19±0.95g). Blood and serum sampling was carried out on 0th day, 14th day, 28th day and 42th day of feeding trials to determine NBT levels, myeloperoxidase activity, phagocytic activity and serum lysozyme activity, as compared to the control group. Fish were challenged with Aphanomyces invadans after 42 days and mortalities were recorded over 18 days post infection. The results revealed that fishes fed with Mikania cordata extract showed significant (p<0.05) increase in NBT levels, myeloperoxidase activity, phagocytic activity and serum lysozyme activity when compared to the control group. Dietary M. cordata extract of 2% showed significantly (p<0.05) higher protection relative percentage survival (RPS 71.06± 5.773%) from A. invadans infection than control. These results indicate that M. cordata leaf powder stimulates the non-specific immunity and makes L. rohita more resistant to fungal infection (A. invadans).
Keywords: Mikania cordata; Aphanomyces invadans; Labeo rohita; immune response